1995
DOI: 10.1111/j.1365-2273.1995.tb01603.x
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal lysine aspirin in recurrent nasal polyposis

Abstract: Twenty patients with recurrent nasal polyposis but without any history of aspirin sensitivity were given 2000 micrograms of intranasal lysine aspirin to one nostril and saline to the other once a week for periods of up to 15 months. Two patients had increased nasal obstruction following the initial test doses of lysine aspirin and were excluded from the trial proper. In the remainder symptomatic polyp recurrence was delayed compared with the previous experience while on intranasal steroids, with eight patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 4 publications
1
16
0
Order By: Relevance
“…The potential effectiveness of topical LAS in the prevention of recurrence of nasal polyps after surgery has already been reported24 29 and our preliminary results have substantially been confirmed by other authors 30. The present study provides further evidence of the effectiveness of LAS treatment following surgery in patients with nasal polyposis, and demonstrates also the favourable effects of LAS in patients who did not have surgery even though surgery was indicated.…”
Section: Discussionsupporting
confidence: 88%
“…The potential effectiveness of topical LAS in the prevention of recurrence of nasal polyps after surgery has already been reported24 29 and our preliminary results have substantially been confirmed by other authors 30. The present study provides further evidence of the effectiveness of LAS treatment following surgery in patients with nasal polyposis, and demonstrates also the favourable effects of LAS in patients who did not have surgery even though surgery was indicated.…”
Section: Discussionsupporting
confidence: 88%
“…It would thus appear to be worthwhile to evaluate the relationship between the expression of VEGF within nasal polyps of varying size. Although several different scoring systems to assess the size of nasal polyps have been proposed previously, they including CT and rhinomanometry [31,32], the endoscopic staging system proposed in 1997 by Lildholt et al [12] appears to be one of the most-sensitive methods available to evaluate the relative size of nasal polyps [33]. Thus we elected to use Lildholt et al's [12] method for our study in order to attempt to evaluate the relationship between the level of expression of VEGF and the actual size of nasal polyps.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term follow-up studies have been reported recently [25]. An open study in AT patients demonstrated a reduction in polyp recurrence similar to that given by topical corticosteroids [26]. Our most recent double-blind trial has involved topical LAS or placebo in addition to regular topical fluticasone propionate in AT patients.…”
Section: Aspirinmentioning
confidence: 94%